Fear of Uncertainty Makes You More Anxious? Effect of Intolerance of Uncertainty on College Students’ Social Anxiety: A Moderated Mediation Model - Li, Jie; Xia, Ying; Cheng, Xinying; Li, Shijia (Frontiers in Psychology, 2020)
Purpose This study investigated the relationships among intolerance of uncertainty (IU), social anxiety (SA), rumination, and pessimistic explanatory style (PES) in a sample of college students. Methods Questionnaires were completed by 533 college students. Results Rumination partially mediated the relationship between IU and SA, and PES plays an important role in moderating the direct path (IU→SA) and the first part of the mediation process. When the PES is low, IU predicts SA less strongly but is related to rumination. Conversely, IU in individuals with a high PES predicts SA more directly. Conclusion Rumination plays a mediating role between IU and SA, and the PES moderates the direct path and the first stage of the mediation model.